2015
DOI: 10.1186/s12885-015-1075-6
|View full text |Cite
|
Sign up to set email alerts
|

Circadian variation in plasma 5-fluorouracil concentrations during a 24 hour constant-rate infusion

Abstract: BackgroundVarying the rate of continuous intravenous infusions of 5-fluorouracil (5FU) chemotherapy over a 24-hour period has been reported to improve patient outcomes. It has been hypothesized that circadian variation in drug disposition is a contributing factor. We analyzed 5-FU concentrations during a 24-hour continuous 5-FU infusion.MethodsSixty-four subjects with advanced malignancies including pancreatic, hepatocellular, colorectal as well as other epithelial malignancies and either abnormal hepatic or r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 25 publications
(23 reference statements)
2
15
0
1
Order By: Relevance
“…Evidence exists on circadian changes in 5-FU plasma levels, by prolonged drug infusions (21,24). A higher plasma concentration is observed in the evening, compared with lower levels, in the early morning (15), though studies have had controversial results, in this regard (25). This variability in 5-FU plasma concentration may affect variability in tolerance to the drug and lower therapeutic efficacy (15).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence exists on circadian changes in 5-FU plasma levels, by prolonged drug infusions (21,24). A higher plasma concentration is observed in the evening, compared with lower levels, in the early morning (15), though studies have had controversial results, in this regard (25). This variability in 5-FU plasma concentration may affect variability in tolerance to the drug and lower therapeutic efficacy (15).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, Cyc significantly correlated with pretherapeutic leucocyte counts: Lower leucocyte counts had greater effects on the magnitude of plasma 5-FU level elevation in the second cycle. Higher 5-FU concentrations in the plasma after repeated treatment with 5-FU in animals and patients have been reported (4,5,13,14). This 5-FU elevation is related to a decrease in clearance and hepatic dihydropyrimidine dehydrogenase (DPD) activity levels (13,14).…”
Section: Final Model Bootstrap (N=1000) ----------------------------mentioning
confidence: 96%
“…However, circadian variations in the plasma 5-FU concentration were observed during continuous infusion of 5-FU, and the repeated treatment cycle also affected the plasma 5-FU concentration, thereby complicating the analysis of the degree to which these factors affect plasma 5-FU concentrations. These effects make it difficult to analyze the data (5) Association between circadian and chemotherapeutic cycle effects on plasma concentration of 5-fluorouracil and the clinical outcome following definitive 5-fluorouracil/cisplatin-based chemoradiotherapy in patients with esophageal squamous cell carcinoma and to determine appropriate blood sampling time points and plasma 5-FU levels. In our previous study, to normalize the circadian rhythm and the treatment cycle effects on plasma 5-FU concentration, an eight-point average value was used to investigate the association with the clinical response (3).…”
Section: Introductionmentioning
confidence: 99%
“…A phase I study investigating 24-h 5-FU and LV levels showed systemic fluctuations in drug concentrations depending on the time of day despite a constant rate infusion [26]. These geneticbased circadian rhythms modulate metabolism and distribution in normal tissues.…”
Section: Intravenous Infusionmentioning
confidence: 99%